Three unusually divergent new genera of phorid flies (Diptera: Phoridae) from Costa Rica - Kung, Giar-Ann; Brown, Brian V. (Zootaxa, 2005)
Three new genera and species, Laciniomyia dilata, Laishania angustithorax, and Tabelliphora teretipenna are described from female specimens collected in Costa Rica. All are classified in the subfamily Metopininae, amongst which they are among the most structurally unusual forms found in the New World.